Evidence for the Use of Mucus Swabs to Detect Renibacterium salmoninarum in Brook Trout - Riepe, Tawni B. (Pathogens, 2021)
Efforts to advance fish health diagnostics have been highlighted in many studies to improve the detection of pathogens in aquaculture facilities and wild fish populations. Typically, the detection of a pathogen has required sacrificing fish; however, many hatcheries have valuable and sometimes irreplaceable broodstocks, and lethal sampling is undesirable. Therefore, the development of non-lethal detection methods is a high priority. The goal of our study was to compare non-lethal sampling methods with standardized lethal kidney tissue sampling that is used to detect Renibacterium salmoninarum infections in salmonids. We collected anal, buccal, and mucus swabs (non-lethal qPCR) and kidney tissue samples (lethal DFAT) from 72 adult brook trout (Salvelinus fontinalis) reared at the Colorado Parks and Wildlife Pitkin Brood Unit and tested each sample to assess R. salmoninarum infections. Standard kidney tissue detected R. salmoninarum 1.59 times more often than mucus swabs, compared to 10.43 and 13.16 times more often than buccal or anal swabs, respectively, indicating mucus swabs were the most effective and may be a useful non-lethal method. Our study highlights the potential of non-lethal mucus swabs to sample for R. salmoninarum and suggests future studies are needed to refine this technique for use in aquaculture facilities and wild populations of inland salmonids.